Extrarenal calyces: A rare anomaly of the renal collecting system - Nataraju G; Nandeesh B; Gayathri M (Wolters Kluwer Medknow Publications, 2009)
The abnormalities of the renal collecting system represent a complex and often confusing subset of urological anomalies. They manifest in many ways and often make preoperative diagnosis difficult. Extrarenal calyces (wherein the calyces and renal pelvis lie outside the renal parenchyma) is one of the rare anomaly of the collecting system. This anomaly may be associated with other anomalies of the urogenital system. We describe in this case report an unusual case of extrarenal calyces with five long calyces draining a hydronephrotic kidney with associated ureteral atresia. Radiological investigations failed to clearly define these abnormalities. The present case helps in understanding the characteristics of a rare, complex anomaly of the urinary system.